STUDI DESKRIPTIF INOVASI E-RETRIBUSI PASAR - M., Maria Magdalena; Sediyono, Eko; Marwata, - (KRITIS, 2020)
The Salatiga City Government has launched an electronic market levy (market e-retribution) which is implemented by the Salatiga City Trade Office. Market e-retribution is an electronic market retribution management system innovation to improve the quality of services that are transparent and accountable, minimize revenue leakage and illegal levies, as well as orderly irregularities in market retribution for compulsory levies. Market e-retribution is included in the regional non-cash transaction implementation agenda in the City of Salatiga. The application of new market e-retribution innovations was carried out in two traditional markets, namely Blauran I Market and Pasar Raya I as a pilot project before being implemented in other traditional markets. This article is a qualitative research with a descriptive approach. This article will focus on discussing the innovation of market e-retribution in the City of Salatiga.